UMP, Terra Drone collaborate to improve expertise in air mobility technology - Mimi Rabita, Abdul Wahit (2021)
KUANTAN, 6 August 2021 - The development of air mobility technology requires the cooperation of all parties in expanding research and development (R&D) activities in areas related to drone technology in line with the transformation of automation technology that will affect the future workforce.